Why Antibiotics cannot be the Main Treatment for Acute Pneumonia - Igor Klepikov* (Archives of Community Medicine and Public Health, 2025)
Abstract It has been known for almost two millennia that the inflammatory process of an organ disrupts its function, which determines the specificity of the clinical picture of the disease. Antibiotics can only have a selective antimicrobial effect but do not directly affect the mechanisms of the inflammatory process. The ability to suppress one of the initial factors of inflammation creates more favorable conditions for the body to fight inflammation. The first successes of antibiotics created the illusion of their decisive role in the treatment of inflammatory processes. Over time, under the influence of antibiotics, the etiology of pneumonia changed, and pathogens that are not included in the spectrum of action of antimicrobial drugs became leaders. This situation already now determines the urgent need for an urgent radical revision of the strategy in the treatment of pneumonia.